ELECTRICAL RESISTIVITY GROUND IMAGING (ERGI): A NEW TOOL FOR MAPPING THE LITHOLOGY AND GEOMETRY OF CHANNEL-BELTS AND VALLEY-FILLS - Baines D.; Smith D.G.; Froese D.G.; Bauman P.; Nimeck G. (My University, 2002)
Efforts to map the lithology and geometry of sand and gravel channel-belts and valley-fills are limited by an inability to easily obtain information about the shallow subsurface. Until recently, boreholes were the only method available to obtain this information; however, borehole programmes are costly, time consuming and always leave in doubt the stratigraphic connection between and beyond the boreholes. Although standard shallow geophysical techniques such as ground-penetrating radar (GPR) and shallow seismic can rapidly obtain subsurface data with high horizontal resolution, they only function well under select conditions. Electrical resistivity ground imaging (ERGI) is a recently developed shallow geophysical technique that rapidly produces high-resolution profiles of the shallow subsurface under most field conditions. ERGI uses measurements of the ground's resistance to an electrical current to develop a two-dimensional model of the shallow subsurface (<200 m) called an ERGI profile. ERGI measurements work equally well in resistive sediments ('clean' sand and gravel) and in conductive sediments (silt and clay). This paper tests the effectiveness of ERGI in mapping the lithology and geometry of buried fluvial deposits. ERGI surveys are presented from two channel-fills and two valley-fills. ERGI profiles are compared with lithostratigraphic profiles from borehole logs, sediment cores, wireline logs or GPR. Depth, width and lithology of sand and gravel channel-fills and adjacent sediments can be accurately detected and delineated from the ERGI profiles, even when buried beneath 1-20 m of silt/clay.
Keywords: CHANNEL-BELTS; CHANNEL-FILLS; ELECTRICAL RESISTIVITY; FLUVIAL SEDIMENTS; SHALLOW GEOPHYSICS; VALLEY-FILLS